Model Peran Lembaga Riset dalam Sistem Inovasi Frugal sektor Pertanian : Pendekatan Analisis Berpikir Sistem - Mahra Arari Heryanto; Dika Supyandi (Center for Science and Technology Development Studies, Indonesian Institute of Sciences, 2012)
As a system, agriculture is a growth engine related to each other: on-farm, off-farm and supporting sub systems. Capital and innovation are main driver of the integrated agriculture (agribusiness system). Hitherto,innovations in agribusiness system (especially on-farm) are still based on farmers’ conventional experiences, which become learning materials that are accumulated into farmers’ knowledge. However, farmer experiences need a long time period and spends a great expense (learning cost), which results in uncompetitive agricultural products related to cost and quality. Agricultural research institutions are still not be able to produce significant innovations for farmers. By the presence of research institution, learning cost and time period can be more efficient, not burden farmers which will reduce farmers' income. Conception-adoption model of ST (science and technology) in agribusiness system is the main structure in frugal innovation system that one of its objectives is to produce competitive and qualified agricultural products. Research institution in the agricultural frugal innovation plays a strategic role as agricultural ST conception-adoption accelerator which is efficient and innovative. As a result, farmers can produce high quality products in low cost and high productivity and affect to the farmers income improvement. In practice, these efforts can be delivered by multiply interaction mechanism between farmers and researchers of research institutions in the development of ST agricultural innovation. The next step can be improved as an action research, which means that any research produced must be applied and each activity applied should be a research based.